Influência da castração na mobilização de leucócitos induzida pelo fator estimulante de colônia de granulócitos (G-CSF) em ratos - Freitas, Rubia Mara Pevidor Pereira de (2010)
Background. The granulocyte colony-stimulating factor (G-CSF) is a hematopoietic cytokine able to stimulate the proliferation, differentiation, maturation and survival of the cell granulocytic lineage. Recently G-CSF has been used in the therapy of several diseases by its capacity to stimulate the mobilization of bone marrow stem cells to peripheral tissues. Furthermore, G-CSF exerts also anti-apoptotic and proangiogenic effects. However, few studies reported the influence of sex differences on the effects of this cytokine. Aims. Our purpose was to compare the effects G-CSF dependent leukocyte mobilization on male and female rats and to further investigate the influence of castration on this process. Methods: Male and female Wistar rats (12 to 14 weeks old) received single dose of G-CSF (50µg/kg, sc), or vehicle and total leukocyte count was performed before (baseline), 3, 6, 12, 18 and 24h later on. Another group received the same G-CSF dose for 7 days and the count was performed in the same period after the last dose. To evaluate the response to the GCSF after myocardial infarction, animals (infarcted or sham) received the same dose of G-CSF or vehicle 30 min after acute myocardial infarction and count was performed 12h later. To verify influences of sex hormones, 3 weeks old male and female rats were castrated and 4 weeks later were treated with G-CSF to determine kinetic of leukocyte mobilization. Results. The leukocyte count was significantly higher in males 6, 12, 18 and 24h after a single dose of G-CSF, reaching the peak with 12h. The number of circulating neutrophils was also higher in males. After seven daily doses, the count was also higher in males, 12h after the last dose. After myocardial infarction, the same difference was found. Surprisingly, in castrated animals, the leukocyte count was also higher in males, 12h after the dose. However, the count of circulating neutrophils was reduced. Conclusions. G-CSF-induced leukocyte mobilization was higher and faster in male rats and castration did not influence the sex dimorphism observed in the effect of this citokyne.